Pengaruh Penggunaan Lumpur Sawit Fermentasi dengan Jamur P. chrysosporium dalam Ransum terhadap Performans Ayam Broiler - Noferdiman, Noferdiman (Fakultas Peternakan Universitas Jambi, 2009)
The experiment was aimed to determine the effect of palm oil sludge fermentation by P. Chrysosporium (LSFp) in ration on the performance of broiler chicken. The experiment was assigned into Completely Randomized Design (CRD) with 5 treatments and 4 replications. The treatments were level of LSFp into the ration (R0 : 0%, R1 : 5 %, R2 : 10 %, R3 : 15 % and R4 : 20 %). The observed variables were the feed consumption, body weight gain, feed conversion ration, carcass percentage, the percentage of abdominal fat, meat fat, meat cholesterol. The result of this study showed that added LSFp were significantly (P<0.05) body weight gain, and carcass percentage. The experiment showed the that fermentation of palm oil sludge (LSFp) could be fed to the broiler chicken up to 15 %.